The Development of Polylactic Acid (PLA) C-Channel Connector - HAIRUL ANUAR, MUHAMMAD HARIZ ISKANDAR; ZAKARIA, NURHUSNA ILYANA; ATAN, NURUL ATIQA NAJWA; SUPAR, KHAIRI (Multidisciplinary Applied Research and Innovation, 2026)
In this project, an innovative modular connector created especially forC-channel truss systems in construction is presented. Conventionalinstallation techniques like welding, screwing, and manual alignmentare time-consuming, frequently need skilled labor, and present safetyhazards on the job site. In order to overcome these obstacles, aconnector was created with AutoCAD software and manufactured via3D printing using PLA (polylactic acid) material, which is renowned forits excellent dimensional correctness, durability, lightweight nature,and environmental sustainability. The connector offers structuralversatility and ease of installation by supporting a variety of truss angleconfigurations, such as 90°-45°-45°, 126°-27°-27°, and 140°-20°-20°.Vernier calipers were used for dimensional verification in a fitment testto assess the connector's precision alignment and compatibility withtypical C-channel profiles. The findings demonstrated that theconnector provides a firm, secure fit without the need for sophisticatedequipment or trained workers, thereby cutting down on assembly timeand enhancing installation consistency overall. PLA is biodegradable,therefore using it not only makes the connector economical andrecyclable, but it also encourages sustainable building approaches. Thisstudy offers enhancements in efficiency, structural performance, andenvironmental effect while illustrating a workable, secure, and scalablesolution for contemporary construction needs. Additionally, it createsnew avenues for future study into alternative thermoplastic materials,3D printing integration into structural engineering applications, andmodular joint design optimization.